2015
DOI: 10.1186/s12955-015-0316-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smoking-specific and generic quality of life measures in current and former smokers in Germany and the United States

Abstract: BackgroundHealth-related quality of life (QOL) surveys include generic measures that enable comparisons across conditions and measures that focus more specifically on one disease or condition. We evaluated the psychometric properties of German- and English-language versions of survey scales representing both types of measures in samples of current and former smokers.MethodsTQOLIT™v1 integrates new measures of smoking-specific symptoms and QOL impact attributed to smoking with generic SF-36 Health Survey measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The significant correlations seen between smoking-specific measures and general measures in current smokers as compared to weaker correlations among former smokers support the validity of TQOLITv1 in measuring the effects of current smoking. The pattern of significant correlations at baseline between general and smoking-specific measures observed in this trial for the German translation is similar to the pattern observed for the English language version of TQOLITv1, 33 suggesting that the results regarding construct validity are generalizable.…”
Section: Discussionsupporting
confidence: 76%
“…The significant correlations seen between smoking-specific measures and general measures in current smokers as compared to weaker correlations among former smokers support the validity of TQOLITv1 in measuring the effects of current smoking. The pattern of significant correlations at baseline between general and smoking-specific measures observed in this trial for the German translation is similar to the pattern observed for the English language version of TQOLITv1, 33 suggesting that the results regarding construct validity are generalizable.…”
Section: Discussionsupporting
confidence: 76%
“…Although any self-report bias is unlikely to account for the superior discriminant validity observed for QDIS over generic measures, QDIS should be evaluated in relation to more objective clinical criteria, which are also likely to make interpretation guidelines more useful clinically. Examples of more independent clinical validation include a recent trial using QDIS with attribution to smoking; QDIS correlated substantially higher with four biomarkers of smoking exposure [ 78 ] and discriminated between current and former smokers much better [ 79 ] than generic SF-36v2® Health Survey measures. Similarly, QDIS with attribution to kidney disease discriminated across clinically-defined stages of CKD better than the SF-12 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a disease-specific questionnaire may provide more precise indications of the true impact of infertility [45], the use of a general questionnaire like the SF-36 provides an ultimately subjective evaluation of health-related QoL in general. The SF-36 is one of the most widely used questionnaires in the literature of infertility [41,46], and it is still currently considered one of the most reliable instruments for the assessment of health-related QoL, in both general and specific clinical populations [47][48][49], also within the perinatal period [50,51]. Therefore, the choice of this questionnaire may allow, for future researchers, to deepen the comparisons on QoL across different clinical populations.…”
Section: Discussionmentioning
confidence: 99%